Analysis of Chemistry Education Students' Level of Understanding of the Basic Concepts of Science Education in the Perspective of Sustainable Maritime Education - Fitriani Rita; Rasyid Muhamad Al; Sabekti Ardi Widhia; Putri Steva Dara (SHS Web of Conferences)
The Basics of Science Education course plays an important role in equipping prospective teacher students with basic concepts of Natural Science which build their understanding of nature and scientific principles. In an effort to support the sustainability of the coastal environment, the integration of sustainable maritime education in learning is an innovative approach. This research aims to analyze the level of understanding of undergraduate students in chemistry education regarding the basic concepts of science education from the perspective of sustainable maritime education. The type of research used was quantitative descriptive with data obtained through the Mid-Semester Examination in the form of 30 multiple choice questions, which were taken by 28 students. Based on the results of data analysis, the average score obtained by students was 19.36 out of a maximum score of 30, with a median score of 19, and the range of student scores was between 7 and 26 points. These findings indicate variations in the level of student understanding of the basic concepts of science education in the context of relevant and sustainable maritime education. The results of the research show that student teacher candidates have varying understandings of the topics taught. This analysis provides insight that efforts are needed to prepare prospective teachers who not only master the basic concepts of science material, but are also able to apply them in the context of sustainable maritime education.